Distribution Strategy of Subsidized Fertilizer in Smallholder Oil Palm Plantation at Air Batu Subdistrict, Asahan District, North Sumatra - Evand, Yogi; Chalil, Diana; Ginting, Rahmanta (Talenta Publisher, 2019)
Palm oil is an important commodity for Indonesia. It is an export oriented commodity with the highest export income contribution. Initially, Indonesian palm oil plantations were developed by major companies and since 1986, smallholders have started to establish. In 2018, the share of smallholders has reached 42% of the total Indonesian oil palm plantation areas. However, unlike major companies, most smallholders’ lack capital. Unfortunately, oil palm smallholders are not in the priority list of subsidized fertilizer recipients. As a result, smallholders have an average productivity that is still lower than private and state company plantations, which are 585.3 ton/ha/year and 5828 ton/ha/year, respectively. This does not only influence smallholder income but also the Indonesian palm oil industry. Therefore, this study will analyze subsidized fertilizer distribution for oil palm smallholders in Air Batu Subdistrict, Asahan District, which are determined purposively as one of the oil palm smallholding centers in North Sumatera. Data were collected from 1 (one) staff of the Agriculture office in Asahan, 2 (two) extension agents, 4 (four) fertilizer shopkeepers, and 24 smallholders in Air Batu. The agriculture office staff and extension agents were selected by purposive sampling based on their knowledge and responsibility in the distribution of subsidized fertilizers while shopkeepers and smallholders were selected with snowball sampling technique. Aside from timeliness, the overall distribution of subsidized fertilizer in Air Batu, Asahan is relatively good. Internal factors are negative since weaknesses are more dominant than strengths, while external factors are positive, since opportunities are more dominant than threats. The Asahan Agriculture Staff have made some fundamental changes, namely improving the management system both internally and externally. Therefore, they can use their strengths to overcome their weaknesses and threats to utilize the available opportunities as well as possible.